"It's our turn (not) to learn": The pitfalls of education reform during post-war institutional transformation - Emily Dunlop; Yasmine Bekkouche; Philip Verwimp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
In this study, we investigate the relationship between education reform, institutional legacies of inequality, and changing political institutions in a poor, conflict-affected country. Burundi experienced a dramatic change in ethnic power relations after the 1993-2005 civil war. The post-war government prioritized education to previously marginalized regions and ethnic groups, both in access and in attainment. We leverage test score data from four nationwide exams in primary and secondary education from 2006 to 2018. Our difference-in-differences analysis shows a dramatic shift in test scores, with the schools in the north of the country, deprived before the civil war, outperforming schools in the south. Results are robust across datasets. We derive policy implications for understanding how post-conflict governments can build inclusive institutions through education after conflict, and how governments can overcome institutional legacies of educational inequality.
Keywords: C22; I24; I25; 330; education reform; difference-in-differences; inclusive institutions; educational inequality; legacies of inequality